Development of hollow fiber membranes with high power density for pressure retarded osmosis - Chen, Yunfeng (2018)
Energy shortage and water scarcity are worldwide challenges, which drive the exploitation of sustainable alternative energy sources. Among various options, osmotic energy has attracted much attention in recent years as a renewable energy that could be harvested by a pressure retarded osmosis (PRO) process, where energy is produced when water permeates naturally from a low salinity stream to pressurized high salinity stream. However, challenges like concentration polarization, membrane fouling and lack of commercial PRO membranes have greatly impeded the practical application of PRO process for energy harvesting. Therefore, proper design of optimized PRO modules with high performance is vital for practical PRO operations. Firstly, a novel thin-film composite hollow fiber PRO membrane with high PRO performance was fabricated. As the hollow fiber membrane is made from polymeric materials, it may gradually deform over time under high pressure loading, or membrane “creeping”, where hollow fiber membranes are severely stretched due to applied pressure in the lumen and thus lose its selectivity, will occur. An attempt to analyze the membrane creeping phenomenon was conducted. The membrane creeping was evaluated via nanoindentation by using an atomic force microscopic (AFM) technique. A non-stop 200 hours PRO test and integrity evaluation were carried out to investigate the membrane performance under various operating pressures. The results showed that the membrane was able to produce a stable power density output of 19.2 W/m2 at 15.0 bar, using 1.0 M NaCl as the draw solution and DI water as the feed water. Membrane creeping was observed when the applied pressure exceeded the safe operation limit or the flux turning point, where the membrane flux started to increase with increasing applied pressure in the PRO mode. This caused an irreversible damage to the membranes. Essentially, this work identified a safe operating boundary for the in-house produced PRO hollow fiber membranes so as to achieve optimized PRO performances. It also provides guidance for practical applications of polymeric hollow fiber membranes in the PRO process. Secondly, the feasibility of the produced PRO membranes for practical PRO operation was examined. It was found that the fouling was severe when a real wastewater retentate from a local water reclamation plant was used as the feed solution of the PRO process. Therefore, low pressure nanofiltration (NF) pretreatment was adopted to treat the wastewater brine prior to feeding it into the PRO process. Three NF membranes were compared in terms of their membrane properties, quality of the NF permeates (i.e., PRO feed) and PRO membrane performances. Results showed that the PRO water flux could increase to 30.5 L/m2h at 16 bar applied pressure by using in-house made low-pressure NF hollow fiber membranes on the pretreated solution, in contrast to a lower water flux of 9 L/m2h in the case of untreated wastewater retentate. A systematic analysis of the water chemistry and various membrane characterization such as electron dispersed X-ray (EDX) and X-ray photoelectron spectroscopy (XPS) depth profiling has revealed that calcium salts, organic compounds, and silica were main contributors of membrane fouling in the PRO process. Low-pressure NF was found to be able to mitigate the fouling potential from multivalent ions and organic matters, but silica scaling in PRO remains a challenge which needs to be further addressed. Furthermore, the PRO membranes were also scaled-up to a two-inch module from a lab-scale half-inch module for a pilot-scale study. The produced PRO modules have a maximum effective area of 0.5 m2. By assessing the PRO performances of the modules with different sizes, external concentration polarization (ECP) was found to have significant impact on the flux reduction during module scale-up. Different module designs, including fiber bundles, distribution baffles and distribution tubes, were thus adopted as an attempt to boost the membrane performance. A power density of 8.9 W/m2 at 15 bar was obtained using tap water as feed and 1M NaCl solution as draw solution. PRO was also carried out using the developed two-inch module on a pilot-scale setup with actual wastewater retentate as feed solution. Low pressure nanofiltration was selected as the pretreatment of the wastewater retentate to mitigate fouling. A power density of larger than 8 W/m2 was obtained when pretreated wastewater retentate was used as the feed solution, implying high potential of PRO in the pilot scale. Nevertheless, full potential of PRO can only be realized by mitigating ECP, which could be achieved by proper module designs and will be conducted in the further endeavor.